PEMBELAJARAN IPA BERASASKAN PENGETAHUAN TEMPATAN TANAMAN FALOAK (Sterculia quadrifida R.Br) SEBAGAI SOLUSI PEMBELAJARAN IPA DI SEKOLAH DASAR - Norazilawati Abdullah; Uslan (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2022)
This paper aims to disclose the relationship of local wisdom owned by the Timor Island community, especially the city of Kupang and the competence that must be possessed by an educator who wants to combine science learning in elementary school with local wisdom. The method used is the literature review through reviewing related reference in the form of theory and research findings in scientific articles. The result obtained shows that the local knowledge can be integrated into modern natural sciences (IPA) learning in elementary school. The steps that the teachers may use in applying local potential in natural sciences (IPA) learning material in elementary school can be carried out by adjusting to the framework of the sociocultural study of education. The integration process of local wisdom in natural sciences teaching can be done by cultivating and a combination process. The expected benefit is to make natural sciences (IPA) more interesting to be studied at the elementary school level and to facilitate students to describe the concept of modern natural sciences (IPA) by applying the local knowledge around the school environment or residence